Screening for HBV, HCV, HIV and syphilis infections among bacteriologically confirmed tuberculosis prisoners: An urgent action required - Puga, Marco Antonio Moreira (PLoS One, 2019)
Viral hepatitis, syphilis, HIV, and tuberculosis infections in prisons have been identified globally as a public health problem. Tuberculosis (TB) and viral hepatitis co-infection may increase the risk of anti-tuberculosis treatment-induced hepatotoxicity, leading to the frequent cause of discontinuation of the first-line anti-tuberculosis drugs. Therefore, the aim of this cross-sectional study was to investigate the epidemiological features of HCV, HBV, syphilis and HIV infections among bacteriologically confirmed tuberculosis prisoners in Campo Grande (MS), Central Brazil. The participants who agreed to participate (n = 279) were interviewed and tested for the presence of active or current HCV, HBV, syphilis and HIV infections. The prevalence of HCV exposure was 4.7% (13/279; 95% CI 2.2–7.1). HCV RNA was detected in 84.6% (11/13) of anti-HCV positive samples. Out of 279 participants, 19 (6.8%; 95% CI 4.4–10.4) were HIV co-infected, 1.4% (4/279, 95% CI 0.5–3.8) had chronic hepatitis B virus (HBsAg positive) and 9.3% (26/279, 95% CI 6.4–13.4) had serological marker of exposure to hepatitis B virus (total anti-HBc positive). The prevalence of lifetime syphilis infection (anti-T. pallidum positive) was 10% (28/279, 95% CI 7.0–14.2) and active syphilis (VDRL ≥ 1/8 titre) was 5% (14/279, 95% CI 2.9–8.3). The prevalence of TB/HCV co-infection among prisoners with HIV (15.8%) was higher than among HIV-non-infected prisoners (3.8%; P<0.05). These results highlight the importance of hepatitis testing among prisoners with bacteriologically confirmed case of TB who can be more effectively and safely treated in order to reduce the side effects of hepatotoxic anti-TB drugs.